Handling of Illegal, Unreported and Unregulated (IUU) Fishing - Pedrason, Rodon; Kurniawan, Yandry; Purwasandi, Purwasandi (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2016)
This research aims are to discuss the maritime diplomacy practice between Indonesia and Malaysia. Problem within the territory of those respective countries, through cooperative maritime diplomacy approach. Thus, by using this design, this study tried to develop the building block of anti-IUU Fishing practiced cooperation between Indonesia – Malaysia. This research used a qualitative approach with descriptive research methods and research techniques using literature study. The result showed that Indonesia – Malaysia maritime diplomacy practice in bilateral framework has not been being the focus in tackling such IUU Fishing. The issue of IUU Fishing is a real threat for both countries, which can affect the economic and security matters. The IUU Fishing activity is transnational which do not have a space for unilateral maritime safety approach. In short, both Indonesia and Malaysia should take a serious measurement through cooperative maritime diplomacy to tackle IUU Fishing problem.